DISMISSAL OF CONSTITUTIONAL JUDGES DURING THEIR TERM OF OFFICE: INTERVENTION EFFORTS TO JUDICIAL INSTITUTIONS - Fajjari, Sahida Ayu; Nasution, Mirza; Sihombing, Eka NAM (EKSEKUSI, 2025)
Proposing the position of Constitutional judge from 3 (three) branches of power to guarantee the independence of the Constitutional Cout ar as  a Defender of Constitution On September 29 2022, the DPR RI proposed dismissing MK judge Aswanto in the middle of his term of office on the grounds that he often disappointed the DPR. Aswanto, who was elected by the DPR, was the subject of dismissal which raised questions regarding the independence and impartiality of the Constitutional Court (MK). This article aims to discuss how proposals for the dismissal of Constitutional Judges should be carried out in accordance with the mandate of Law Number 7 of 2020, and to emphasize that the Constitutional Court has no obligation to be responsible for the proposing institution. As a result, there is no place for the removal process of judges while they are still in tenure due to political considerations in implementing judicial policies.